USM TO FOCUS ON ADVANCED RESEARCH, HIGHIMPACT COLLABORATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 3 June 2015 – Universiti Sains Malaysia (USM) will focus on strengthening advanced research and enhancing its academic programmes to ensure that they are of international standard. USM ViceChancellor, Professor Dato’ Dr. Omar Osman stated that USM will also strengthen high impact collaboration with its strategic partners from all over the world, in line with its aspirations to drive higher education for the future.